Fighting the Islamic state : what about the day after? - James M. Dorsey (2014)
The 'US' military operations against Islamist jihadists in Iraq and possibly Syria risk repeating the West's failure to embed kinetic interventions in post-conflict reconstruction policies to address the core grievances of populations in the Middle East and North Africa.